1993
DOI: 10.1097/00002341-199309000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Management of Traumatic Optic Neuropathy—A Study of 23 Patients

Abstract: Twenty three patients with traumatic optic neuropathy were managed by medical and surgical treatment as follows. High dose intravenous steroids were initiated in all patients. If visions did not improve significantly after 24 to 48 hours decompression of an optic nerve sheath haematoma by medial orbitotomy and neurosurgical decompression of the optic canal were considered based on computed tomographic scan findings. Nine of 16 patients who received steroids only showed significant improvement. One of three sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 7 publications
1
26
0
1
Order By: Relevance
“…Retrospective reports of the use of high-dose steroids are also subject to similar criticisms. [14][15][16] The natural history of traumatic optic neuropathy has not been studied prospectively, but several authors have reported that spontaneous recovery may occur in at least a third of patients. [17][18][19] There has been no randomised, placebo-controlled study of patients with indirect optic nerve injury.…”
Section: Treatment Of Indirect Optic Nerve Injurymentioning
confidence: 99%
“…Retrospective reports of the use of high-dose steroids are also subject to similar criticisms. [14][15][16] The natural history of traumatic optic neuropathy has not been studied prospectively, but several authors have reported that spontaneous recovery may occur in at least a third of patients. [17][18][19] There has been no randomised, placebo-controlled study of patients with indirect optic nerve injury.…”
Section: Treatment Of Indirect Optic Nerve Injurymentioning
confidence: 99%
“…There were reports in the TON case literature of 0-48% 3-7 rate of spontaneous improvement, 44-82% 8,9 rate of improvement with varying doses of steroid treatment, and 37-71% 10-13 rate of improvement with surgical optic nerve decompression. The 2001 International Optic Nerve Trauma Study (IONTS), 14 the only prospective international observational study, and the recent TON Cochrane reviews 15,16 did not recommend a standardized investigation or treatment protocol.…”
Section: Introductionmentioning
confidence: 99%
“…In the past three decades, there have been a total of seven cases of successful treatment of TON with enlarged optic nerve/sheath in imaging through ONSF (Goldenberg-Cohen et al, 2004;Guy et al, 1989;Hupp et al, 1984;Mauriello et al, 1992;Muthukumar, 1997;Sergott et al, 1990). The detailed clinic course, imaging and surgical findings were compared with our two cases in Table 1 (Table 1).…”
Section: Discussionmentioning
confidence: 99%